Chhoti Car, Badhe Sapne (Small Car,Big Dreams):Building Brands and Launching of a New Product - Maheshwari, Nidhi (Indian Journal of Marketing, 2009)
The brand not only enables a business to focus its efforts around all the needs of the customer (functional, psychological and social), but it also provides the language, which articulates that relationship. It is the definable social area in which customer activity moulds with the communication and marketing mixes developed by the marketer. A brand is therefore a "statement of psychological relationship and dependency between a customer and a marketer". Marketing communications is a systematic relationship between a business and its market in which the marketer assembles a wide variety of ideas, designs, messages, media, events, shapes, forms and colors, both to communicate his ideas to, and to stimulate a particular perception of products and services amongst the target market. The result of this process of assembling is referred to by marketers as the communications mix. To assemble this mix, the marketer uses a number of marketing communications tools such as: direct marketing, advertising, sales promotions, public relations, point of purchase collateral, events and marketing design like logos, stationery etc.